Together we make the neighbourhood: Citizen spatial appropriation strategy response in the context of the covid-19 crisis. Case of Madrid self-managed community spaces - Arana, Juan (Sens public)

(untitled) (Département des littératures de langue française, 2024)
A network of various self-managed community spaces played a crucial role in the citizen-led response to the social crisis during the first months of the COVID-19 crisis in the most vulnerable neighbourhoods in the periphery of Madrid. Nevertheless, such community spaces are under a precarious situation due to recurrent threats of closure from different administrations. It is therefore crucial to make visible the importance posed by such spaces in the construction of more resilient, equitable, and caring neighbourhoods. To that end, we propose the definition of a theoretical model of critical placemaking to understand how such grassroots practices are underlaid by a collective project of neighbourhood. The research fills the gap within different theories of placemaking, social innovation, and urban commons to establish a model based on the three axes: community, space, and political project. The study draws from the notions of relational place and civic engagement, together with models of space appropriation and social innovation theory. The theoretical model is contrasted with the qualitative research of the cases of social centres La Villana de Vallekas and Eko de Carabanchel. The results suggest an emergent city model at the neighbourhood scale of proximity self-managed citizen-led infrastructure that configures a resilient network against systemic and external threats.